2011
DOI: 10.3892/ijmm.2011.716
|View full text |Cite
|
Sign up to set email alerts
|

The otoferlin interactome in neurosensory hair cells: Significance for synaptic vesicle release and trans-Golgi network (Review)

Abstract: Abstract. Sound perception in terrestrial vertebrates relies on a structure in the inner ear consisting of the utriculus, sacculus and lagena. In mammals, the lagena has developed into the cochlea where mechanotransduction at ciliated cells leads to ion influx via regulated ion channels. To maintain proper Ca 2+ concentration many cellular systems use a variety of functional proteins; the neurosensory systems use calcium-sensors like hippocalcin, visinin or recoverin. In cochlear hair cells the 230 kDa protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…34,35 The cytoplasmic leaflet of the Golgi membrane contains PI4P, and we therefore sought to test for the effects of calcium on C2F–PI4P binding by titrating phospholipid membranes composed of PC, PS, and PI4P in the absence and presence of calcium (Figure 8). In the absence of calcium, the C2F domain bound liposomes with a K d value of 29.1 ± 4.39 μM.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The cytoplasmic leaflet of the Golgi membrane contains PI4P, and we therefore sought to test for the effects of calcium on C2F–PI4P binding by titrating phospholipid membranes composed of PC, PS, and PI4P in the absence and presence of calcium (Figure 8). In the absence of calcium, the C2F domain bound liposomes with a K d value of 29.1 ± 4.39 μM.…”
Section: Resultsmentioning
confidence: 99%
“…The auditory system involves the perception and enhancement of sound signals, as well as transformation of the mechanical signals to ion fluxes in inner hair cells. Management of the electric signals to the brain involves a series of nerve channel openings [18]. Genetic mutations in the gene encoding otoferlin ( Otof ) cause a clinical, autosomal recessive nonsyndromic form of prelingual and sensorineural deafness [19][21].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, otoferlin expression has an inverse correlation with the peripheral NK cell count. Low NK cell count has been associated with an increase in disease activity of the orbital myositis [ 26 ]. In addition, a recent study has shown that children with JDM have lower than normal NK cell counts, particularly after the onset of the COVID-19 pandemic [ 27 ].…”
Section: Discussionmentioning
confidence: 99%